Galanin receptors (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Galanin receptors (provisional nomenclature as recommended by NC-IUPHAR [56]) are activated by the endogenous peptides galanin and galanin-like peptide. Human galanin is a 30 amino-acid non-amidated peptide [51]; in other species, it is 29 amino acids long and C-terminally amidated. Amino acids 1–14 of galanin are highly conserved in mammals, birds, reptiles, amphibia and fish. Shorter peptide species (e.g. human galanin-1–19 [21] and porcine galanin-5–29 [166]) and N-terminally extended forms (e.g. N-terminally seven and nine residue elongated forms of porcine galanin [22, 166]) have been reported.